Mass transfer of a thermally radiative MHD Cattaneo-Christov nanofluid between two stretchable spinning disks - Habu, Peter Ngbo; Sharifah Nuriza Al’Aidrus,; Noor Fadiya Mohd Noor,; Zailan Siri, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The investigation on the impacts of magnetic field, thermal radiation, generation of heat and mass transfer in a porous-medium-embedded homogenous nanofluid flow between two stretchable spinning disks is crucial since spinning disks are prevalent in many engineering and technological applications. The objective of this research was to analyze the influences of these parameters using the Cattaneo-Christov heat flux model against the flow’s temperature, velocity and concentration profiles. Temperature profile is a decreasing function of thermal relaxation time parameter due to the particles require a longer period to transfer heat to the next particles. The rates of heat transfer at both spinning disks decrease as values of heat generation, Eckert number, Prandtl number, Brownian diffusion, thermophoresis diffusion and rotation ratio increase. The disks’ rates of mass transfer decrease with more thermophoresis diffusion, heat generation, heat transfer dissipation, and momentum diffusivity, but they increase with thermal radiation parameter. The current work attempts to include the transport profile of a Buongiorno’s nanofluid embedded in a Darcian porous medium between dual spinning disks with magnetic field, thermal radiation and generation of heat using the heat flux model of Cattaneo-Christov’s. Von Karman transformations are utilized to transform the nonlinear partial differential equations of fluid dynamics into coupled nonlinear ordinary differential equations (ODEs). These coupled ODEs are later solved by employing a shooting method with MATLAB bvp4c algorithm. All numerical evidences from this investigation are conferred through tables and figures after validation of present computations.